NORMAL ELEMENT ON IDENTIFY PROPERTIES - Titi Udjiani; Solikhin Zaki; Suryoto Suryoto; Harjito Harjito (Diponegoro University, 2018)
One type of element in the ring with involution is normal element. Their main properties is commutative with their image by involution in ring. Group invers of element in ring is always commutative with element which is commutative with itself. In this paper, properties of normal element in ring with involution which also have generalized Moore Penrose invers are constructed by using commutative property of group invers in ring.